Prospects of halal tourism development in West Kalimantan Province, Indonesia - Ita Nurcholifah; Barkah .; Erna Listian; Fachrurazi . (International Journal of Islamic Business and Economics (IJIBEC))
This study aims to reveal the prospects of halal tourism development to obtain opportunities in West Kalimantan. This study used a qualitative method with a phenomenological approach. The research data were collected through interview, observation, and documentation which were then analyzed using NVivo 12 Plus. The prospects of halal tourism in West Kalimantan Province were seen from the development of four aspects: destination, marketing, industry, and institution. The high prospects of promising halal tourism in West Kalimantan, must be the primary development focus. Some development direction aspects including destination, marketing, industry, and institution, should be studied and prioritized in the Regional Tourism Master Plan (known as RIPDA/Rencana Induk Kepariwisataan Daerah). Supports in the form of funding, facility, and certification are greatly required to immediately realize halal tourism in West Kalimantan. The appropriately managed halal tourism, in turn, can increase revenue for both region and community. NVivo 12 Plus analysis tool can show priority aspects should be focused by the local governments. The research methods and models can be used the further researchers in their future research on halal tourism.